Identification of Barriers in Performing Physical Activities in Children with Autism Spectrum Disorder (ASD) - Anggre Lia Sukma; Jajat; Kuston Sultoni (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to identify and compare physical activity barriers in children with Autism Spectrum Disorder (ASD) and children with non-ASD disabilities based on parental perceptions. Using a comparative quantitative design with a cross-sectional approach, the research involved 56 respondents, consisting of 29 children with ASD and 27 children with non-ASD disabilities aged 6–17 years, with a gender distribution of 33 males and 23 females. The instrument used was the Barriers to Being Active Quiz (CDC, 1999), and data analysis was conducted using the Independent Sample T-Test with α = 0.05. Results showed significant differences in four categories of barriers: social influence (p = .000), lack of energy (p = .003), lack of willpower (p = .000), and lack of injury (p = .000). Children with ASD were more hindered by internal factors such as low motivation and self-regulation difficulties. Conversely, children with non-ASD disabilities were more affected by physical and environmental barriers, including fear of injury, fatigue, and lack of social support. No significant differences were found in three other categories: lack of time, lack of skill, and lack of resources. These findings emphasize the need for physical activity interventions tailored to the characteristics of each group of children with special needs.